2016
DOI: 10.1111/grs.12131
|View full text |Cite
|
Sign up to set email alerts
|

Ecotypic variation in forage nutrient value of a dominant prairie grass across a precipitation gradient

Abstract: Ecotypic variation in forage nutrient value of a dominant grassland species, Andropogon gerardii Vitman (big bluestem), was quantified across a longitudinal precipitation gradient of the US Great Plains. Ecotypic variation of A. gerardii has been documented across this gradient, but the extent to which forage nutrient value differs among ecotypes is poorly known. Seven indicators of forage nutrient value (neutral detergent fiber [NDF], acid detergent fiber [ADF], in‐vitro dry matter digestibility [IVDMD], crud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
2
8
0
Order By: Relevance
“…Previous studies have demonstrated that the environmental factors including climate and soil fertility have a great effect on the forage quality traits, such as fibers, protein content, and digestibility (Buxton, 1996;Robins et al, 2015). In agreement with our results, the variation in nutritive value traits such IVDMD, ADF, and CP is significantly influenced by monthly and annual precipitation among the populations of the forage grass Andropogon gerardii (Gibson et al, 2016;Mendola et al, 2015). The populations of B. hybridum analyzed in our study span along a precipitation gradient from the north to the south and along gradient of soil salinity and fertility from the coast to the continent.…”
Section: Significant Associations Between Environmental Factors and The Variation Of Forage Quality Traits Under P Deficiencysupporting
confidence: 92%
“…Previous studies have demonstrated that the environmental factors including climate and soil fertility have a great effect on the forage quality traits, such as fibers, protein content, and digestibility (Buxton, 1996;Robins et al, 2015). In agreement with our results, the variation in nutritive value traits such IVDMD, ADF, and CP is significantly influenced by monthly and annual precipitation among the populations of the forage grass Andropogon gerardii (Gibson et al, 2016;Mendola et al, 2015). The populations of B. hybridum analyzed in our study span along a precipitation gradient from the north to the south and along gradient of soil salinity and fertility from the coast to the continent.…”
Section: Significant Associations Between Environmental Factors and The Variation Of Forage Quality Traits Under P Deficiencysupporting
confidence: 92%
“…Of all common garden designs, reciprocal transplant studies, where populations from spatially separated habitats are cross‐transplanted, have provided some of the most valuable insights into adaptive variation, selection and local adaptation (Savolainen et al., 2013). Numerous studies indicate local adaptation is a common phenomenon that is best investigated with reciprocal transplant platforms (Gibson, Espeland, et al., 2016; Gibson, Donatelli, et al., 2016). This approach is the main focus of this review.…”
Section: Historical Foundation For Reciprocal Gardens: the Last Centurymentioning
confidence: 99%
“…In contrast, drought can also have inconsistent or even negative effects on CP contents, a change that is mostly associated with high drought severity Deleglise et al, 2015Wang & Frei;. Drought is also known to decrease NDF and ADF contents (Bittman et al, 1988;Gibson et al, 2016;, but here, there are also contradicting reports Deleglise et al, 2015;. Drought increases WSC contents .…”
Section: Introductionmentioning
confidence: 80%
“…Decreasing fibre content during dry periods or under unstable water supply has been reported often (Bittman et al, 1988;Bruinenberg, 2002;Gibson et al, 2016;, although contrary results exist . A decrease is mostly explained by delayed maturation and thus less cell wall material in the physiologically younger plant Küchenmeister et al, 2013), but could also be a result of lacking N supply, because N uptake and thus growth was inhibited under drought .…”
Section: Drought Stressmentioning
confidence: 89%
See 1 more Smart Citation